A generalisable integrated natural capital methodology for targeting investment in coastal defence. Issue 4 (2nd October 2019) - Davis, Katrina J.; Binner, Amy; Bell, Andrew; Day, Brett; Poate, Timothy; Rees, Siân; Smith, Greg; Wilson, Kerrie; Bateman, Ian
ABSTRACT: Coastal ecosystems, such as saltmarsh, produce a range of ecosystem services that underpin human well-being. In the UK, and globally, saltmarsh extent and quality is declining due to coastal squeeze, deteriorating water quality, and agricultural activities. Here, we develop a general framework to evaluate changes in coastal defence. Using this framework, we identify priority areas for saltmarsh re-alignment: re-creation of saltmarsh in areas that have been saltmarsh in the past – but that have been claimed for a variety of land uses, particularly agriculture. We base our re-alignment prioritisation on the ecosystem services provided by saltmarsh in the North Devon Biosphere Reserve: specifically carbon sequestration and recreational benefits, and the economic values of those services. We compare potential economic benefits with the economic costs of creating new saltmarsh areas – specifically lost agricultural output, property damages and direct re-alignment costs. We identify a number of priority areas for managed re-alignment that generate high recreational values in areas where properties would not be damaged. These findings provide a necessary and timely analysis for the managers of the North Devon Biosphere Reserve. Furthermore, we outline a comprehensive methodology to plan future management of coastal zones.